Implementasi Budaya 5S Sebagai Upaya Pembentukan Karakter Siswa - Shema Andi Prasetya (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
5S culture is self- habituation to always (Senyum, Sapa, Salam, Sopan, and Santun). This study aims to get a clearer and more complete picture and information regarding the attitudes of students in schools in implementing 5S culture. The research subjects were students of SMA batik 1 Surakarta, SMA Muhammadiyah 1 Surakarta, and SMA Muhammadiyah 3 Surakarta. This type of research uses qualitative methods through a case study approach. The result of the research is that students implement the 5S culture even though in certain conditions they are still exceeding the limit.